Association of dietary inflammatory index with obesity among children and adolescents in the United States NHANES cohort: a population-based study - Lili Zhang; Huimin Peng; Yao Wang; Hongjun Ba (BMC, 2024)
Abstract Background Childhood obesity has become a huge challenge to childhood health, and there is a lack of understanding about the relationship between dietary inflammatory index (DII) and childhood obesity. The main objective of this study was to analyze the potential link between DII and obesity among children and adolescents residing in the United States. Methods A cross-sectional analysis was performed using data obtained from the National Health and Nutrition Examination Survey between 2009 and 2018. In total, 12,454 participants were included in the analysis. DII was calculated based on dietary data from the first day of the 24-hour dietary recall. Logistic regression was used to analyze the association between DII and obesity, as well as central obesity defined by the waist-to-height ratio of 0.5 or higher or waist circumference ≥ 90th percentile for age and sex. Results The mean dietary inflammation index was 2.05 (SE = 0.02), with higher levels in children than in adolescents (P = 0.01). According to our findings, the prevalence of central obesity was higher among adolescents (38.0%) than among children (31.4%). The adolescents in the third quartile of DII have a higher risk of overweight/obesity (OR = 1.46, 95% CI: 1.24-1.71) after adjusting for age, sex, and race. This positive association remained significant even after physical activity was added to the model. Concerning central obesity, the adolescents in the highest quartile of DII have a higher risk, independent of demographic characteristics and physical activity. However, no significant association was observed among children. Conclusions The dietary inflammation index was positively associated with overweight/obesity and central obesity among adolescents in the United States after adjusting for confounding factors. These findings highlight the importance of promoting anti-inflammatory diets in adolescents to prevent obesity and its associated complications.